La economía de los blindajes, los planes y las anticrisis - Cárdenas Núñez, Gilberto José Rafael (2009)
A plan anti deficient crisis places in the uncertainty to the future economic development to Peru. The inaction has been replaced by the improvisation. The measures that the Government programs hardly will have the results that are expected.